Development and Comparison of Two Multiresidue Methods for the Determination of 17 Aspergillus and Fusarium Mycotoxins in Cereals Using HPLC-ESI-TQ-MS/MS - Scarpino, Valentina; Reyneri, Amedeo; Blandino, Massimo (Frontiers in Microbiology, 2019)
Cereals can be contaminated by several mycotoxins, whose co-presence may represent an undervalued risk for humans and animals. Maize and wheat are the most contaminated cereals and in temperate areas could be affected in field conditions by several Fusarium and Aspergillus infections. To date, only B-fumonisins (FBs), aflatoxins (AFs), zearalenone (ZEA), deoxynivalenol (DON) and T-2 and HT-2 toxins have been regulated in cereals in European Union. The other fungal metabolites, are commonly referred to as "emerging" and “masked” mycotoxins, and more information on their occurrence in combination with the regulated mycotoxins, are needed to design combined toxicological and exposure assessments. This research intends to develop and compare two multiresidue HPLC-ESI-TQ-MS/MS methods for the simultaneous determination of the main regulated, emerging and masked mycotoxins in maize and wheat, among which: FB1, FB2, DON, ZEA, AFB1, AFB2, AFG1, AFG2, MON, DON-3-G, 3-acetyldeoxynivalenol, 15-acetyldeoxynivalenol, nivalenol, enniatins (ENNA, ENNA1, ENNB, ENNB1). The extraction was performed for both methods using a mixture of CH3CN/H2O/CH3COOH (79/20/1, v/v/v), while the dilution/purification was carried out through two different procedures: 1) by the "dilute-and-shoot" technique diluting 1:2 the filtered extract with CH3CN/H2O/CH3COOH (20/79/1, v/v/v) to reduce the matrix effect; 2) using the Oasis® PRiME HLB clean-up columns. The analysis was carried out using CH3OH and H2O both acidified with 0.1% of CH3COOH as eluents. The injection volume was 20 μL and the flow rate 200 μL min-1. The analysis of 2 reference material (maize and wheat), was performed to evaluate the trueness and precision of the two methods by matrix-matched calibration curves. For all the regulated mycotoxins analyzed by both methods, the range of recovery percentage established by the Regulation (EC) No. 401/2006 was respected, except for ZEA by using the Oasis® PRiME HLB clean-up columns. Nevertheless, the results suggest that the Oasis® PRiME HLB clean-up columns, could be a valid alternative to the dilute-and-shoot method, although an additional cost for the clean-up has to be considered. In conclusion, both two analytical methods considerably reduce the analytical time and costs and therefore result to be promising and applicable for high-throughput routine multi-mycotoxins analysis by the use of a TQ.